Evaluating the ecological influence of hydraulic projects: A review of aquatic habitat suitability models. (February 2017) - Yi, Yujun; Cheng, Xi; Yang, Zhifeng; Wieprecht, Silke; Zhang, Shanghong; Wu, Yingjie
Abstract: In order to evaluate the ecological influence of hydraulic projects, aquatic habitat suitability modeling was proposed. Compared with other environmental flow methods, this method, for the first time, integrated considering hydrology parameters and ecology attributes, quantitatively describing the relationships between species and habitat. Aquatic habitat suitability models began with one-dimensional physical habitat simulation model (PHABSIM) at micro-scale physical habitat. Afterwards, habitat suitability models for meso- and macro-scale were developed; eco-factors indicating physical habitat and water quality situation were included; two- and three-dimensional model were employed to provide the situation of eco-factors. Based on field survey or mathematical models, the state of habitat eco-factors can be obtained. By establishing habitat suitability evaluation criteria, the impact of aquatic habitats on the particular life stage of indicate species can be assessed, the effect of reservoir regulation mode and habitat restoration projections can be predicted. Here, we summarized aquatic habitat suitability models in different spatial scale, and the advantages and disadvantages of each model were analyzed and concluded.